Some Benefits of Using Readers Theatre in EFL Classroom - Angraini, Desti (JURNAL INOVASI EDUKASI, 2019)
Reading plays an important part in developing learners’ knowledge. By reading, learners will get many benefits, such as adding their knowledge, knowing information and having pleasure. There are many ways of making them engaged in learning English especially reading skill. One kind of activities is using Readers’ theatre.  RT was introduced in EFL classroom to enhance the learning of communication skills. Readers’ theater offers learners’ an opportunity for interpretive oral reading as they use voices, facial expressions, and hand gestures to interpret characters in stories. Readers’ theater also builds readers’ confidence, brings stories to life through performance, animates content areas, and improves reading ability, comprehension, and oral reading skills.